Effect of Regular Aerobic Exercise on Vasomotor Symptoms (Hot Flashes) in Postmenopausal Women - B Tartibian; S Sharabiyani; A Abbasi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2009)
BACKGROUND AND OBJECTIVE: Most women that reached menopause, experience vasomotor symptoms (hot flashes). Its main cause, however, is not obvious but some researches have shown that there is a relationship between FSH level and hot flashes. On one way, hormone therapy (HT) has been associated with an increased risk of chronic diseases. Therefore, attention is increasingly focused on managing vasomotor symptoms via physical activity. So this study was done with this purpose to investigate the effects of regular aerobic exercise on vasomotor symptoms (hot flashes) in postmenopausal women.METHODS: In this quasi-experimental study, twenty healthy postmenopausal women with average age of 53.6± 4.3 years, who sampled randomly in 2 groups (control and experimental), were participated in this investigation. The subjects were individuals who had experienced at least five hot flashes per 24 h. The experimental group followed exercise training program including walking (60%-70% of MHR) three times a week, for 10 weeks. But control group did not participate in any exercise program. Blood samples were taken before and after the exercise program to measure FSH concentration by means of RIELE. And so, hot flashes level was measured before and after exercise by means of Kupperman questionnaire and compared.FINDINGS: Mean of serum FSH level and hot flashes in control group before exercise training (52.1±13.8, 9.2±1.93 IU/L respectively) relative to after exercise training (53.4±14.1, 8.8±2.5 IU/L respectively) weren significantly changed. But mean of serum FSH level and hot flashes in exercise group after exercise training (46.1±11.8, 6±2.1 IU/L respectively) relative to before exercise training (51.8±11.1, 9.2±1.93 IU/L respectively) were significantly decreased (p = 0.001).CONCLUSION: The results of present study demonstrated that regular aerobic exercise training decrease serum FSH level and vasomotor symptom. So, the authorities should apply strategies to decrease vasomotor symptoms by changing life style from inactivity to exercise training in order to support postmenopausal women somatic health.